A feasibility study of utilizing tribo-acoustics for mobile user interface - Leong Y.W.; Seki H.; Kamiya Y.; Hikizu M. (2023)
This paper proposes the feasibility of using triboacoustically emitted signals (TES) generated between finger (covered or uncovered) and tracing surfaces (with or without mechanoreceptors) as an input method for mobile users. This is achieved by localizing upon the acoustic signals generated during the net motion between 2 surfaces in contact. This property allows it to be highly versatile in many real life scenarios. The design of the system opportunistically utilizes the microphone's frequency limitations to define its fundamental frequency of 25kHz and the uniqueness of each signal captured to separate the microphones pairs at the 8th subharmonic distance of separation. The system was proven to be feasible and versatile as test results show it could recreate triboacoustically traced shapes when coupled with different types of surface materials. Results show that the acoustical localization system is able to recreate shapes of a tracing event similar to that produced by the visually localized system but at lower precision and accuracy. 2013 IEEE.